ChemInform Abstract: Cleavage of the C=N Bond in Carbodiimides via Release of High Ring Strain: A New Strategy for the Selective Synthesis of 2‐Aminoaryl Alkynyl Imines. Issue 35 (2nd September 2014) - Zhou, Yi; Chi, Yue; Zhao, Fei; Zhang, Wen‐Xiong; Xi, Zhenfeng
Abstract A novel multicomponent reaction of terminal alkynes or haloalkynes, carbodiimides, and benzynes is achieved via cleavage and reorganization of C=N bond to efficiently obtain the title compounds.